2019
DOI: 10.1590/1980-5373-mr-2018-0846
|View full text |Cite
|
Sign up to set email alerts
|

Materials Selection Using a 2-tuple Linguistic Multi-criteria Method

Abstract: The materials selection can affect the design component radically, with effect on the manufacturing systems efficiency, environmental impact issues, and customer satisfaction. There are different methods employed for materials selection; however, two steps are usual for most of these methods: screening and ranking. The ranking step identifies among materials candidates those that can perform the function the best as possible. Multi-criteria methods have been widely employed to materials selection, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A sensitivity analysis was performed to illustrate the effectiveness and robustness of the TOPSIS 2-tuple method for selecting and ranking the most suitable technologies for separating fat from dairy waste. The results derived by the TOPSIS 2-tuple method with those deduced by VIKOR 2-tuple (Wu et al, 2015) and TARGET 2-tuple (Setti et al, 2019) are shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sensitivity analysis was performed to illustrate the effectiveness and robustness of the TOPSIS 2-tuple method for selecting and ranking the most suitable technologies for separating fat from dairy waste. The results derived by the TOPSIS 2-tuple method with those deduced by VIKOR 2-tuple (Wu et al, 2015) and TARGET 2-tuple (Setti et al, 2019) are shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Decision-makers determine each criterion's importance, that is, the weights of the criteria through a set of linguistic variables. The aggregate linguistic weight of the criteria is obtained by Equation ( 5), and the weight of the criteria in the form of real numbers is obtained by Equation ( 6) as proposed by (Setti et al, 2019).…”
Section: Multicriteria Model For Fat Removal From Dairy Wastementioning
confidence: 99%